Metachronous small bowel metastasis from a mixed Müllerian mesodermal tumour - Williamson, JML (Ann R Coll Surg Engl, 2016)
A mixed Müllerian mesodermal tumour (MMMT) is a rare aggressive carcinosarcoma. Metastatic progression is uncommon, and occurs via haematological, lymphatic and intraperitoneal spread. Although the latter is seen most frequently, the small intestine seems to be relatively preserved from disease progression with only one reported case of synchronous involvement. We report a case of metachronous MMMT involvement of the small bowel presenting with subacute obstruction that was successfully resected at operation.